THREAT TO NYONYA CUISINE HERITAGE SUSTAINABILITY IN MALAYSIA: A SYSTEMATIC LITERATURE REVIEW APPROACH - Sakinah Haniff; Siti Ida Isnainie Md Mubin; Mohamad Farhan Azmi; Wan Rusni Wan Ismail (Journal of Islamic, Social, Economics and Development, 2022)
With rich gastronomic culture, Malaysia offers a wide variety of cuisines with uniqueheritage background and identity. Nyonya cuisines for instance emerged from acculturationprocess of two distinctive culture hence creating unique cuisines that only can be found incertain location in Malaysia. This systematic review article focuses on the current state ofliterature related to the development of Nyonya cuisine in Malaysia and aims of this review isto identify the gap in the literature. This research follows Preferred Reporting Items forSystematic Review and MetaAnalysis 2020 (PRISMA - 2020) methodology. This systematicliterature review relies heavily on two major journal databases, Science Direct and Scopus.Indirectly, a total of 14 articles have met the standards to be reviewed systematically. Finally,the review successfully summarized six threats to Nyonya Cuisine Heritage sustainability inMalaysia: weak roles of society, modernization, globalization, tough competition from largermainstream ethnic restaurants, halal status, and cost of living.